Critical thinking and representation skills of biology students: Are they related? - Any Fatmawati; Siti Zubaidah; Sutopo Sutopo; Susriyati Mahanal (JURNAL BIOEDUKATIKA, 2022)
Critical thinking skills are relevant skills in the contemporary industrial 4.0 era. The current study aimed to investigate the correlation between critical thinking and representation skills and the extent to which the two variables are related. This study was conducted at UNDIKMA and UNW Mataram, West Nusa Tenggara, Indonesia between March and August 2020. It involved 62 students from the Department of Biology Education. The research data were gathered using essay questions on Plant Physiology. Data analysis was performed using the Pearson correlation test, followed by a simple linear regression analysis. The statistical analysis showed a correlation between critical thinking and representation skills among biology students (r = 0.948, p < 0.001, N = 62). The correlation was positive with regression equation Y = 12.122 + 0.835x. Therefore, educators are advised to promote critical thinking in the classroom to support student representation skills.